Chemical parameters and bacterial communities associated with larval habitats of Anopheles, Culex and Aedes mosquitoes (Diptera: Culicidae) in western Kenya. (6th June 2016) - Onchuru, Thomas Ogao; Ajamma, Yvonne Ukamaka; Burugu, Marion; Kaltenpoth, Martin; Masiga, Daniel; Villinger, Jandouwe
Abstract: Aquatic larval habitat conditions influence the development, fitness and vectorial capacity of mosquitoes. In turn, human activities can influence these conditions and shape mosquito vector distribution, thus affecting pathogen circulation and transmission. We measured environmental factors (chemical and microbial) in mosquito larval habitats and evaluated their potential as predictors for the occurrence of different mosquito species in an arbovirus and malaria endemic region of western Kenya. We found significantly greater proportions of Aedes aegypti mosquito larvae in ammonium and phosphate rich habitats, suggesting that fertilizer usage could potentially increase aquatic habitat suitability and Aedes vectored disease transmission. Anopheles gambiae larval habitats correlated significantly with higher temperatures. However, none of the Culex species' habitats correlated with investigated variables, indicating greater larval plasticity compared to Aedes or Anopheles . Profiling of bacterial communities by 16S rRNA pyrosequencing revealed Proteobacteria, Bacterioidetes and Firmicutes as the major bacteria phyla present in mosquito aquatic microhabitats. Although there were no correlations between microbiota composition or diversity and larval species abundance, the dominant genera of microbes detected in larval habitats were reported in larval and adult mid-guts, suggesting that bacteria acquired from the larval habitats are transmitted to adult stages. This study identified the chemical and bacterial composition of aquatic microhabitats that are conducive to the development of different mosquito vectors in western Kenya. This information can inform potential vector control strategies by assessing management of breeding sites based on likely exposure to fertilizer, light and bacterial fauna.